"I Don't Shag Dirty Girls": Marginalized Masculinities and the Use of Partner Selection as a Sexual Health Risk Reduction Strategy in Heterosexual Young Men. (March 2016) - Limmer, Mark
Understanding and addressing the sexual risk taking of young men remains a key research, policy, and practice concern in attempts to improve the emotional and physical sexual health of young men and their sexual partners. This article explores one of the ways in which young men attempt to mitigate sexual risk through the assigning of labels to particular young women and using these as a basis for their decisions in relation to sexual activity, contraception, and condom use. The article uses the lens of hegemonic masculinities theory to increase understanding of the role played by the construction and performance of marginalized masculinities and how these in turn are influenced by social exclusionary processes. The article draws on focus group and interview data from 46 young men aged 15 to 17 years living in the northwest of England, purposively selected on the basis of the prevailing policy definitions of social inclusion and exclusion. The article describes a form of marginalized masculinity pertaining to socially excluded young men, which as a result of limited access to other tenets of hegemonic masculinity, is disproportionately reliant on sexual expertise and voracity alongside overt demonstrations of their superiority over women. It is in this context that young women are assigned the labels of "dirty" or "clean" on the basis of a selection of arbitrary judgments relating to dress, demeanor, area of residence, and perceived sexual activities. The motivations of the young men, the impact on young women, and the policy and practice implications are all discussed.